Synthesis of Cationic Surfactant N, N-(2-Laurate-Ethyl) Stearamidium Chloride - Chairuddin (Talenta Publisher, 2021)
The cationic surfactant of N, N-(2-Lauric-Ethyl) Stearamidium Chloride had been successfully synthesized. It is long-chain alkyl surfactant derivative from ammonium salt with amide. Cationic surfactants that are synthesized from fatty acid derivatives are stearic acid and lauric acid. Stearic acid is used as stearamide-making material which is the product of methyl stearate amidation with diethanolamine use methoxide sodium catalyst. Lauric acid was used as esterification material with stearamide thus obtaining N, N-(2-Lauric-Ethyl) Stearamide of alcanolamide ester. Alcanolamide ester continued by salting reaction use HCl gas until obtained cationic surfactant of N, N-(2-Lauric-Ethyl) Stearimidium Chloride. Each compound analyzed function groups by FT-IR spectrophotometric with the analyzed change of melting points, and a part compound analyzed surface tension characteristic with measuring Critical Micelle Concentration (CMC) with use Du Nouy ring method. The analysis product obtained shows that methyl stearate by yield in the amount of 91.66% shows that melting point of 40.5°C, stearamide with yield in the amount of 87.6% show that melting point as 185°C by CMC value 0.133 mol/ L in 40.7 dyne/cm surface tension. Alcanolamide ester with a yield in the amount of 84.7% has a melting point of 55°C by a CMC value of 0.067 mol/L in 36.1 dyne/cm surface tension, and cationic surfactant has a melting point of 45°C by CMC value 0.055 mol/L in 31,1 dyne/cm surface tension. stearamide with a yield in the amount of 87.6% show that melting point of 185°C by a CMC value of 0.133 mol/L in 40.7 dyne/cm surface tension. Alcanolamide ester with a yield in the amount of 84.7% has a melting point of 55°C by a CMC value of 0.067 mol/L in 36.1 dyne/cm surface tension, and cationic surfactant has melting point as 45°C by CMC value 0.055 mol/L in 31,1 dyne/cm surface tension. stearamide with a yield in the amount of 87.6% show that melting point of 185°C by a CMC value of 0.133 mol/L in 40.7 dyne/cm surface tension. Alcanolamide ester with a yield in the amount of 84.7% has a melting point of 55°C by a CMC value of 0.067 mol/L in 36.1 dyne/cm surface tension, and cationic surfactant has a melting point of 45°C by CMC value 0.055 mol/L in 31,1 dyne/cm surface tension.